Marker of lipid peroxidation related to diabetic nephropathy in Indonesian type 2 diabetes mellitus patients. Issue 1 (April 2015) - Sauriasari, R.; Andrajati, R.; Azizahwati; Dharmeizar; Saputri, D.A.; Muris, R.U.; Manfaatun, A.; Amanda, O.F.; Setiawan, H.; Sakano, N.; Wang, D.H.; Ogino, K.
Highlights A significant correlation between 8-iso-PGF2α and eGFR in T2DM patients. Increasing level of MDA was mildly correlated with the decline in eGFR (MDRD). Increasing UACR inversely correlate with eGFR (corrected-CG, MDRD, and CKD-EPI). Increased 8-iso-PGF2α and MDA in T2DM patients may play a role in the pathophysiologic significance of diabetic nephropathy, in which 8-iso-PGF2α contributes in the initiating process.